Time domain analysis of flyback EMI based on distributed parameters theory - Liu, Baiyi; Li, Rui; Ji, Jianqiang; Wang, Yiming; Xu, Po (Frontiers in Electronics, 2025)
The electromagnetic interference (EMI) is a key issue for most of electric or electronic devices, the researches of suitable analysis methods and solutions absorb much attentions. The research about electromagnetic interference (EMI) is normally based on two approaches (i.e., time domain analysis and frequency domain analysis). The frequency domain analysis is easier to apply theoretical model to analyze the circuit loop impedance of EMI noise which can provide guidance of EMI suppression, but it cannot reflect the real amplitude of EMI noise without the real waveforms of noise sources. The time domain analysis is usually based on circuit simulation to get the EMI noise directly, but it is time consuming. In order to combine the advantages of these two approaches, this paper proposes a high frequency equivalent circuit model of flyback converter and analyze the effect of each distributed parameters on the common mode (CM) and differential mode (DM) noise. The experimental result verified the accuracy and efficiency of the proposed method, which not only can correctly reflect the real waveforms of the circuit, but also can predict the EMI noise based on the constructed waveforms.